Issues of internal control during the reform period - Shynkarenko, V. I.; Gresova, O. I.; Gresova, Y. G. (Science and Transport Progress, 2012)
The paper considers theoretical and methodological problems of organization and financial control activities, the main problems and reasons causing the need for a unified system of internal financial control in the State Administration of Railway Transport of Ukraine at the stage of the reform.